The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pssc.201000969
|View full text |Cite
|
Sign up to set email alerts
|

Achieving high‐growth‐rate in GaN homoepitaxy using high‐density nitrogen radical source

Abstract: The key issue in GaN growth by radio‐frequency plasma‐assisted molecular beam epitaxy is the low growth rate compared with that obtained using an ammonia source. To reduce the processing time and to improve the crystalline quality of the epilayer, a high‐density radical source (HDRS) with high stability has been developed. The growth rate of the GaN epilayer was improved using the HDRS rather than a conventional radical source. During the growth, a sharp streak pattern obtained by reflection high‐energy electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 3 publications
(3 reference statements)
0
45
0
Order By: Relevance
“…Though we have presented mainly pulsed metal deposition data, the observations made also have implications for conventional film growth with plasma sources. For instance, our results may explain an apparent inconsistency observed by Kawai et al 43 who, for a 1000 fold increase in active nitrogen species from a new MBE plasma source, were only able to achieve a factor of 3 increase in GaN growth rate. Beyond that increase they also observed gallium droplet formation.…”
Section: -9mentioning
confidence: 46%
“…Though we have presented mainly pulsed metal deposition data, the observations made also have implications for conventional film growth with plasma sources. For instance, our results may explain an apparent inconsistency observed by Kawai et al 43 who, for a 1000 fold increase in active nitrogen species from a new MBE plasma source, were only able to achieve a factor of 3 increase in GaN growth rate. Beyond that increase they also observed gallium droplet formation.…”
Section: -9mentioning
confidence: 46%
“…Recent report suggested that the surface structure of the GaN films are highly affected by the Ga/N flux (i.e. plasma power at constant Ga flux) [14]. Fig.…”
Section: Methodsmentioning
confidence: 97%
“…[7]) for transition 3 P2à 3 S1 at l0 =130.2 nm can be converted in s (1) (n0) = 1.83×10 -13 cm 2 that gives R (1) = 1.20x10 12 Hz. For the unresolved two-photon transition 3 P2à 3 P2,1,0 at l0 = 225.6 nm the (includes G (2) =2, see next section) [29] can be converted to s (2) (v0) = 4.84×10 -46 cm 4 s that gives R (2) = 6.24x10 4 Hz. Although the two-photon absorption is much less probable than the one-photon absorption, fluorescence signals are easily detectible.…”
Section: Two-photon Absorption Ratementioning
confidence: 99%